Assessment of attention and working memory among young adults using computer games - Basu, Saikat; Saha, Sudipta; Das, Sourav; Guha, Rajlaksmi; Mukherjee, Jayanta; Mahadevappa, Manjunatha (Journal of ambient intelligence and humanized computing, 2023)
Cognitive controls are a set of interrelated mental skills. Academic and professional successes require proper coordination of these skills. Young generations suffer from cognitive deficits due to their addiction to the internet and computer games. To resolve their mental health crisis, it is essential to understand the individuals’ cognitive abilities and impairments. Existing tasks to measure mental abilities are mostly either paper–pencil-based or desktop computer-based. We have developed a novel system named ‘Montaj’ in a handheld device for carrying out psychological tests and assessing cognitive skills. Cognitive skills measuring psychological tasks were embedded in this system. We have done gamification of these tasks and presented them to subjects as a gaming platform. As the existing research on cognitive abilities focused mainly on preschool or school children, we have studied variations of cognitive skills among young adults with different demographics like age, gender, and institutes using the scores of our game-based software containing four cognitive games. We have used a unique and combined scoring system to measure cognitive functions. One hundred forty-three students from two different institutions were examined using these games. The scores of the first three games were compared with the scores of the last game, which embeds the Stroop task to correlate attention and working memory measures. We recommend only a few game levels for measuring attention and working memory based on a positive correlation with the Stroop task. A composite score has been proposed using analytic hierarchy process and technique for order of preference by similarity to ideal solution.